2005
DOI: 10.1107/s1600536805012237
|View full text |Cite
|
Sign up to set email alerts
|

Pyrimethaminium sulfosalicylate monohydrate

Abstract: Key indicatorsSingle-crystal X-ray study T = 273 K Mean (C-C) = 0.004 Å R factor = 0.036 wR factor = 0.106 Data-to-parameter ratio = 12.9For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 8 publications
(8 reference statements)
0
19
0
Order By: Relevance
“…The sulfonate O atoms mimic the role of the carboxylate group in generating the R 2 2 (8) ring motif (Bernstein et al, 1995;Etter, 1990). A similar type of interaction of the PMN cation with a sulfonate group has been reported (Hemamalini et al, 2005;Nirmalram & Thomas Muthiah, 2010). Base pairing via N4B-H4B1Á Á ÁN3A i and N4A-H4A1Á Á ÁN3B vi hydrogen bonds (see Scheme 4 and Table 13) generates a quadruple DADA array with the fused-ring motifs R 2 3 (8), R 2 2 (8) and R 3 3 (10) ( Fig.…”
Section: Table 13mentioning
confidence: 54%
“…The sulfonate O atoms mimic the role of the carboxylate group in generating the R 2 2 (8) ring motif (Bernstein et al, 1995;Etter, 1990). A similar type of interaction of the PMN cation with a sulfonate group has been reported (Hemamalini et al, 2005;Nirmalram & Thomas Muthiah, 2010). Base pairing via N4B-H4B1Á Á ÁN3A i and N4A-H4A1Á Á ÁN3B vi hydrogen bonds (see Scheme 4 and Table 13) generates a quadruple DADA array with the fused-ring motifs R 2 3 (8), R 2 2 (8) and R 3 3 (10) ( Fig.…”
Section: Table 13mentioning
confidence: 54%
“…It selectively binds with DHFR enzyme through several hydrogen bonds (Hitchings & Burchall, 1965). The crystal structures of PMN (Sethuraman & Muthiah, 2002), PMN sulfosalicylate monohydrate (Hemamalini et al, 2005) and PMN benzoate complexes (Stanley et al, 2005) have been reported from our laboratory. The present study has been undertaken to study the hydrogen-bonding patterns in pyrimethaminium 3-chlorobenzoate (PMMB), (I).…”
Section: Commentmentioning
confidence: 93%
“…Table 5. ) and four other CSD entries [refcodes GAMFAC (Hemamalini et al, 2005), MUFMAB (Sethuraman & Thomas Muthiah, 2002), ULAXIO (Sethuraman et al, 2003) and VEVNIU (Devi, Muthiah, Bocelli & Cantoni, 2006)].…”
Section: Figurementioning
confidence: 99%